The advantage of virgin soil in rural service road constructions - Ćwiąkała, Michał; Greinert, Andrzej; Korzeniowska, Joanna; Tarasewicz, Paweł (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
Virgin soils as a result of geotechnical processes are element of road’s solid bottom. The bottom ought to have enough capacity and durability which is provided by proper virgin sub-grade’s enhancement. The sub-grade is road’s base course right bottom. It is possible to improve virgin soil’s parameters by road’s hydraulic binding agent. The agent is a mineral frame’s micro-particle extender or enhancement. The researches were focused to define main soil-cement compound’s mechanical parameter called CBR. Compounds consisted of rural virgin soils (five grain-size types) and two hydraulic agent types (endurance rates 3 MPa and 9 MPa). Hydraulic agent’s main component was activated fly ash and white cement (CEM I 42,5 MPa). The ash is from Pątnów Power Plant and is a result of brown coal burning. The researches answered that it is possible to exploit virgin soils in rural service road’s construction thanks to innovative road cements with binding qualities.